Prevalence and characterization of ESBL-producing diarrheagenic Escherichia coli from the poultry industry in Shanghai, China - Que, Fengxia; Yuan, Jiachun; Xu, Xinyue; Liu, Chunfu; Yang, Yunyan; Ye, Yulong (Frontiers in Microbiology, 2025)
ObjectiveAntibiotic resistance genes (ARGs) in bacteria are highly prevalent in the poultry industry. These genes can transfer not only within the same species but also across different species, posing significant threats to both the poultry industry and human health. However, limited research has been conducted on the prevalence and transmission links between extended-spectrum beta-lactamase (ESBL)-producing diarrheagenic Escherichia coli (E. coli) in chickens and their living environments in Shanghai’s poultry industry.MethodsIn this study, 600 samples were collected from the cloacal swabs of healthy chickens and from the environments of poultry farms. These samples included feces, troughs, water containers, and soils. Antimicrobial susceptibility testing and whole-genome sequencing (WGS) were employed to characterize ESBL-producing diarrheagenic E. coli.ResultsThe results indicated a detection rate of E. coli at 15.67%, with the isolates exhibiting high resistance to the tested antibiotics, particularly ampicillin (AMP),nalidixic acid (NAL), chloramphenicol (CHL), and tetracycline (TET). Notably, 95.45% of the isolates were multidrug-resistant (MDR). Among these isolates, 20.45% were ESBL-producing E. coli, which exhibited higher resistance to first- through fourth-generation cephalosporins, such as cefazolin (CFZ),cefuroxime (CXM), and cefotaxime (CTX). These ESBL-producing E. coli also carried a significant number of ARGs, with blaTEM-1B (55.56%) and blaCTX-M-55 (38.89%) being the most prevalent on the farm. The dominant sequence type (ST) was ST1286, the prevalent serotype was O16: H32, and the dominant CH type was FumC174/FimH23. Isolates that shared the same ST types clustered together and exhibited the same serotypes and CH types.ConclusionThe findings from this study reveal that ARGs are widely distributed among ESBL-producing E. coli strains. STs with the same serotypes and FumC-FimH (CH) types showed high genetic relatedness in single-nucleotide polymorphism (SNP)-based phylogenetic analysis, highlighting the need for enhanced surveillance to prevent further transmission.